Growth and Starch Content Evaluation on Newly Released Cassava Cultivars, Rayong 9, Rayong 7 and Rayong 80 at Different Harvest Times - Siripatr Prammanee; Kaettipong Kamprerasart; Suppachai Salakan; Klanarong Sriroth (Agriculture and Natural Resources, 2010)
The objectives of this study were to evaluate the growth and the starch content of cassava at different harvest times for four promoted cultivars (Rayong 5, Rayong 90, Kasetsart 50 and Huay bong 60), three newly released cultivars (Rayong 9 or CMR 35-64-1, Rayong 80 or CMR 35-22-196 and Rayong 7 or CMR 35-21-199) and one variety of CMR 35-55-166. The results showed that the newly released cultivars, Rayong 9 and Rayong 7, had good average growth. However, their plant and fresh root weights were not significantly different from the other cultivars. Huay bong 60 and Rayong 9 tended to have higher average plant and fresh root weights than the other cultivars. Rayong 80 had the highest starch content analysis using the Reimann scale balance method, followed by Rayong 9, Kasetsart 50 and Rayong 7, respectively. The newly released cultivars, Rayong 80 and Rayong 9, had good starch content based on both fresh and dry starch analysis when the roots were harvested at 10 or 12 months after planting. These cultivars could be recommended for growing in Prachinburi province and a suitable harvest time should be 10 or 12 months.